In vivo MRI Successfully Reveals the Malformation of Cortical Development in Infant Rats - Lee, Minyoung; Kim, Eun-Jin; Woo, Dong-Cheol; Shim, Woo-Hyun; Yum, Mi-Sun (Frontiers in Neuroscience, 2020)
Objective: Malformations of cortical development (MCDs) are major causes of intractable epilepsies. To characterize the early neuroimaging findings of MCDs, we tried to identify the MRI features consistent with pathological findings in an infant rat MCD model, prenatally exposed to methylazoxymethanol (MAM), by using newly developed MRI techniques. Methods: At gestational day 15, two doses of MAM (15 mg/kg intraperitoneally) or normal saline were injected into pregnant rats. The offspring underwent in vivo MRI, including glutamate chemical exchange saturation transfer (GluCEST), 1H-MR spectroscopy, and diffusion tensor imaging, at postnatal day (P) 15 using a 7T small-animal imaging system. Another set of prenatally MAM-exposed rats were sacrificed for histological staining. Results: At P15, the retrosplenial cortex (RSC) of rats with MCDs showed decreased neuronal nuclei, parvalbumin, and reelin expressions. Moreover, dendritic arborization of pyramidal cells in the RSC significantly decreased in infant rats with MCDs. In vivo MRI showed significantly decreased GluCEST (%) in the RSC of rats with MCDs (p < 0.001) and a significant correlation between GluCEST (%) and RSC thickness (r = 0.685, p = 0.003). The rats with MCDs showed reduced glutamate (p = 0.002), N-acetylaspartate (p = 0.002), and macromolecule and lipid levels (p < 0.05) and significantly reduced fractional anisotropy values in the RSC. Conclusions: In vivo MRI revealed reduced neuronal population and dendritic arborization in the RSC of infant rats with MCDs during the early postnatal period. These pathological changes of the cortex could serve as clinical imaging biomarkers of MCDs in infants.